EARTHQUAKE HAZARD ANALYSIS OF NGANJUK REGENCY - Wisyanto, Wisyanto; Sri Naryanto, Heru (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Earthquake hazard must be considered by many regions in Indonesia. This is including Nganjuk Regency, the area with intensifies development and where the longest dam in Indonesia is being built. Earthquake hazard studies are conducted using two methods, namely semi-deterministic and probabilistic methods. The results of analyses using the first method show that Nganjuk Regency can be divided into 3 classes of hazards, low level in the southwest region, middle level in the north and high level in the middle of the region. Analyses using the second method reveal that Nganjuk Regency can be classified into two categories, the southwest region which has the potential to experience very strong shocks with an intensity of upper VII MMI to lower VIII MMI and the northern and central region which has the potential of destructive shocks with an intensity of middle VIII MMI. The difference in the results from the two methods can be eliminated by classifying the detail of the existing soil/rock types.